2022
DOI: 10.24326/asphc.2022.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition phenolic, antioxidant, and bio-herbicidal properties of the essential oil of rosemary (Rosmarinus officinalis L.)

Abstract: The essential oil yield was obtained from the rosemary plant at the rate of 0.93 mL/100 g, and 1,8-cineol, camphor, isoborneol, α-pinene were identified as the highest component. While the total phenolic content in the essential oil of the rosemary plant was 13.87 mg GAE/g (DW) and the IC50 value was 15.02 μg extract mL–1, the DPPH antioxidant activity value was obtained as 38.43%. For the investigation of herbicidal effect of the essential oils on seed germination , different doses (0.5, 1.0, 2.0, 4.0, 8.0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Many studies have demonstrated the potential of essential oils as biopesticides against harmful organisms in agriculture (pests, diseases and weeds) [18,19,25,77,78]. However, phytotoxic properties of EOs have long been a major drawback to their potential widespread applicability, because they may exhibit harmful effects to non-target plants.…”
Section: Phytotoxic Effect Of Essential Oilsmentioning
confidence: 99%
“…Many studies have demonstrated the potential of essential oils as biopesticides against harmful organisms in agriculture (pests, diseases and weeds) [18,19,25,77,78]. However, phytotoxic properties of EOs have long been a major drawback to their potential widespread applicability, because they may exhibit harmful effects to non-target plants.…”
Section: Phytotoxic Effect Of Essential Oilsmentioning
confidence: 99%